FORMULATION AND ANTIBACTERIAL ACTIVITY OF MOUTHWASH COMBINATION OF GUAVA LEAF (Psidium guajava L.) AND BASIL LEAF (Ocinum basilicum L.) EXTRACT AGAINST Streptococcus mutans : FORMULASI SEDIAAN MOUTHWASH KOMBINASI EKSTRAK DAUN JAMBU BIJI (Psidium guajava L.) DAN DAUN KEMANGI (Ocinum basilicum L.) TERHADAP AKTIVITAS BAKTERI Streptococcus mutans - Samsuar, Samsuar; Ariawan, M Wahyu; Pratiwi, Inda; Widodo, Subur; Susanti, Laila; Luthfiyah, Yosi (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2025)
Dental caries is basically caused by cariogenic bacteria, including Streptococcus mutans, which are found in the oral cavity, especially dental plaque. To treat dental caries, antiseptics packaged in the form of mouthwash use unnatural active ingredients which often cause side effects. Therefore, it is necessary to carry out preventive measures to reduce side effects by using waste from guava leaves and basil leaves. This research purpose were to making mouthwash formulation with the active ingredients guava leaf extract and basil leaf extract and determine the antibacterial activity of mouthwash formulation. The method used is the diffusion method, a combination of concentrations of guava leaf extract and basil leaves, namely F1(0%+20%), F2(5%+15%), F3(10%+10%), F4( 15%+ 5.0%), F5(20%+0%), F6(15%+15%). In this study, the variable measured in this study was the diameter of the inhibition zone formed by the combination of extracts. Data analysis was tested using One Way Anova. The significant value obtained was 0.00 ≤ 0.05, indicating a significant difference from the formulation containing a combination of extracts. The results of this research showed that the largest inhibitory zone was at F5 with the largest average value of 15.07mm which had a strong inhibitory response. This research can be concluded that the mouthwash formulation of extracts meets the physical requirements and can inhibit S. mutans. Keywords : Guava, basil, mouthwash, S. mutans